2019
DOI: 10.1093/cercor/bhz318
|View full text |Cite
|
Sign up to set email alerts
|

Slowly-Conducting Pyramidal Tract Neurons in Macaque and Rat

Abstract: Anatomical studies report a large proportion of fine myelinated fibers in the primate pyramidal tract (PT), while very few PT neurons (PTNs) with slow conduction velocities (CV) (<~10 m/s) are reported electrophysiologically. This discrepancy might reflect recording bias toward fast PTNs or prevention of antidromic invasion by recurrent inhibition (RI) of slow PTNs from faster axons. We investigated these factors in recordings made with a polyprobe (32 closely-spaced contacts) from motor cortex of anest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…10 , bottom). It is well known that extracellular recordings have a bias toward large cells with faster-conducting axons ( Humphrey and Corrie, 1978 ; Kraskov et al, 2019 , 2020 ). An even more extreme bias is likely for intracellular records, as penetrations into small cells are usually rapidly lost because of mechanical instability.…”
Section: Discussionmentioning
confidence: 99%
“…10 , bottom). It is well known that extracellular recordings have a bias toward large cells with faster-conducting axons ( Humphrey and Corrie, 1978 ; Kraskov et al, 2019 , 2020 ). An even more extreme bias is likely for intracellular records, as penetrations into small cells are usually rapidly lost because of mechanical instability.…”
Section: Discussionmentioning
confidence: 99%
“…They are largely missing from the primate neurophysiological literature [ 14 ], most likely because their action potentials are small and difficult to record stably with conventional recording techniques. Newer methods have revealed that it is possible to identify them [ 15 ], and therefore possible to begin to study their function.…”
Section: The Wide Spectrum Of Primate Corticospinal Fibresmentioning
confidence: 99%
“…These estimates should be considered conservative as they assume a monosynaptic connection; in reality, some effects from the corticospinal tract to SC cells will take a more indirect route which would require a larger compensation that the 1 ms synaptic delay which we allowed. Additionally, our dataset of PTN recordings is biased towards the fastest PTNs (Firmin et al 2014;Innocenti et al 2019;Kraskov et al 2018;Kraskov et al 2019). If M1 contributes to SC responses through the many PTNs which are even slower than those recorded here, then M1 contributions to SC responses would be even smaller than assessed here.…”
Section: Do Spinal Cells Respond Directly To the Perturbation Or Indmentioning
confidence: 77%